Serum IgG Is Associated With Risk of Melanoma in the Swedish AMORIS Study - Kessler, Anna; Sollie, Sam; Karagiannis, Sophia N.; Walldius, Goran; Hammar, Niklas; Van Hemelrijck, Mieke (Frontiers in Oncology, 2019)
Background: Relatively little is known about the role of the humoral immune system in melanoma. Tumour infiltrating B cells in melanoma patients have been associated with increased T cell activation in tumours as well as improved patient survival. Immunoglobulins may play an important part in the anti-tumour immune response. We hypothesised that increased levels of pre-diagnostic serum Ig may be protective against melanoma development. Hence, we evaluated associations between pre-diagnostic serum markers of the immunoglobulin A (IgA), IgG and IgM, and risk of developing melanoma in the Swedish Apolipoprotein-related MORtality RISk (AMORIS) study. Methods: Study participants aged ≥20 years with baseline measurements of IgG, IgA and IgM taken between 1985 and 1996 were selected (n=29,876). All individuals were free from melanoma at baseline and 162 study participants developed melanoma during follow up. Cox proportional hazards regression was carried out for medical cut-offs of IgA, IgG and IgM. Results: Compared to the reference level of 6.10-14.99 g/l, we observed a positive but not significant association with risk of melanoma for those with IgG levels <6.10 g/L [HR: 1.05 (95% CI 0.39-2.86)] and an inverse association for those with IgG levels ≥ 15.00 g/L [HR: 0.60 (95% CI 0.34-1.05); Ptrend = 0.08]. No associations with serum IgA or IgM were identified. Conclusions: The humoral response might provide a protective role against the development of melanoma, mediated through IgG. Further research is needed to characterise this response which may be exploitable for development of future therapies.